Karakterisasi Permukaan Pada Aluminium Anodized-Dyed dengan Pewarna Alami Kunyit - Ahmad Muslim; Aris Widyo Nugroho (JMPM (Jurnal Material dan Proses Manufaktur), 2018)
Dyeing on anodizing process can be done with chemical or natural dyes. Indonesia has a variety of useful plants as a natural dye, one of which is turmeric. The purpose of this research is to know the effect of turmeric dye concentration variation on color brightness, macro structure, surface roughness, oxide layer thickness and wear rate on aluminum anodizing result. Aluminum plate with 1.5 mm thick was cut with size of 50 x 30 mm. The plate was performed anodizing process with 2 amperes of current, 12 volt of voltage for 30 minutes. Dyeing was carried out using commercially available turmeric powder. The dyeing process used variations in concentration of 10, 20 and 30 gram per liter of water at temperature of 90-97 ° C for 30 minutes. The coloring results were tested for color brightness by image analysis software, macro structure test and oxide layer thickness using optical microscope and surface roughness test using roughness tester and wear test with Ogoshi method. Test results showed the effect of turmeric concentration variation concentration on color brightness, macro structure, surface roughness and wear rate. The highest color brightness (RGB) is obtained on a variation of turmeric concentration of 10 gram / liter. The surface macro structure showed the existence of homogeneous pores. The most uniform colored staining is obtained on the variation of turmeric concentration of 30 grams / liter. Whilst the highest surface roughness was found on aluminum which had been anodized with variation of turmeric concentration of 30 gram / liter with the value of 1,344 μm, its wear value presents the lowest of 2.07 x 10-10 mm2 / kg. The concentration variation of the dye solution did not affect the thickness of the resulting oxide layer.